Our living oceans : an interactive quide to the seas - UNESCO; National Museum of Natural History (Paris) ([New York] : Emme, 1999)
Presents 16 articles on the history of oceanography, marine ecosystems, and marine biodiversity. Includes interviews with 8 world-renowned scientists, 450 photos, 175 marine fact sheets, 100 species profiles, 3D animations, 45 min. of videos, and internet links for further study.
This set includes two CD-ROMs for the whole famile! :Reference CD-ROM and Junior CD-ROM.
Audience :Ages 12 and up.
System requirements for Windows :Pentium 75 MHz; 16MB RAM; Windows 95/98/ME; 4X CD ROM drive; 640 x480 display; thousands of colors; 16-bit Sound Blaster card or compatible; System requirements for Macintosh: Power Macintosh; 16 MB RAM; Macintosh 7.0+; 4X CD-ROM drive; 640 x 480 display; thousands of colors.
Keywords: CD-ROMs.; Ocean -- Juvenile software; Oceanography -- Juvenile sofware; Marine biology -- Juvenile software